THE INVOLVEMENT OF SANDRO IN ADDRESSING “SALA SINGIN” MENTAL DISORDERS IN THE SUMBAWA COMMUNITY - Arcellya Nova Arditha; Ainurizan Ridho Rahmatullah (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Mental health issues in Indonesia are increasing, but treatment is often constrained by local culture values. This study aims to determine why traditional coping mechanisms are chosen by the people of Sumbawa as a means of dealing with mental disorders in Sumbawa, using a qualitative Research design and a phenomenological approach. This study involved three participants form Sumbawa Regency who had knowledge and experience related to traditional medicine, using purposive sampling. Data analysis using phenomenological descriptive method. The results of study identified three main themes, namely the understanding of the sumbawa community sumbawa community regarding mental disorder, which are interpreted as a problem of disharmony between an individual identity and their soul (Sala singin), challenges in handling this issue including limited understanding of mental health, social stigma, and constraints related to the lack of professional service, and the community strong preference for the Sandro figure as a culturally based coping strategy. Sandro is seen as having spiritual authory that is in line with the traditional belief in Sumbawa. This coping practice is realized throught traditional remedies integrated with the support of local communities. These findings indicate that cultural values form the basis of traditional culture-based treatments that shape an integral adaptation system of local belief.